Role of FGF System in Neuroendocrine Neoplasms: Potential Therapeutic Applications - Giovanni Vitale (Frontiers in Endocrinology, 2021)
Neuroendocrine neoplasms (NENs) are a heterogeneous group of tumors originating from neuroendocrine cells dispersed in different organs. Receptor tyrosine kinases are a subclass of tyrosine kinases with a relevant role in several cellular processes including proliferation, differentiation, motility and metabolism. Dysregulation of these receptors is involved in neoplastic development and progression for several tumors, including NENs. In this review, we provide an overview concerning the role of the fibroblast growth factor (FGF)/fibroblast growth factor receptor (FGFR) system in the development and progression of NENs, the occurrence of fibrotic complications and the onset of drug-resistance. Although no specific FGFR kinase inhibitors have been evaluated in NENs, several clinical trials on multitarget tyrosine kinase inhibitors, acting also on FGF system, showed promising anti-tumor activity with an acceptable and manageable safety profile in patients with advanced NENs. Future studies will need to confirm these issues, particularly with the development of new tyrosine kinase inhibitors highly selective for FGFR.